2018
DOI: 10.3389/fpls.2018.00846
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Volatile Terpenoid Profiling and Transcriptomics Analysis for Gene Mining and Functional Characterization of AvBPPS and AvPS Involved in the Monoterpenoid Biosynthesis in Amomum villosum

Abstract: Amomum villosum, also known as Fructus Amomi, has been used to treat digestive diseases such as abdominal pain, vomiting, and dysentery. Volatile terpenoids are the active metabolites in the essential oil of Fructus Amomi. Nevertheless, downstream genes responsible for activating metabolites biosynthesis in A. villosum still remain unclear. Here, we report the use of an integrative volatile terpenoid profiling and transcriptomics analysis for mining the corresponding genes involved in volatile terpenoid biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 46 publications
2
45
1
Order By: Relevance
“…In this study, we identified a (+)-bornyl diphosphate synthase (CbTPS1) from C. burmannii that catalyzed GPP to form (+)-borneol under the hydrolysis of CIAP. This is the first time an enzyme related to (+)-borneol synthesis was mined from C. burmannii , and it has the highest specificity for (+)-borneol production ( Wise et al, 1998 ; Despinasse et al, 2017 ; Hurd et al, 2017 ; Wang et al, 2018 ). The K m value of CbTPS1 (5.11 μM) for GPP is consistent with SBS (3.0 μM) ( Wise et al, 1998 ) and slightly lower than other reported monoterpene synthases (13.10–26.12 μM), which indicated CbTPS1 had a higher affinity for GPP.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, we identified a (+)-bornyl diphosphate synthase (CbTPS1) from C. burmannii that catalyzed GPP to form (+)-borneol under the hydrolysis of CIAP. This is the first time an enzyme related to (+)-borneol synthesis was mined from C. burmannii , and it has the highest specificity for (+)-borneol production ( Wise et al, 1998 ; Despinasse et al, 2017 ; Hurd et al, 2017 ; Wang et al, 2018 ). The K m value of CbTPS1 (5.11 μM) for GPP is consistent with SBS (3.0 μM) ( Wise et al, 1998 ) and slightly lower than other reported monoterpene synthases (13.10–26.12 μM), which indicated CbTPS1 had a higher affinity for GPP.…”
Section: Discussionmentioning
confidence: 93%
“…It was classified into the TPS-b subfamily, which contains three motifs of typical terpene synthases, namely the RRX 8 W motif responsible for monoterpenoid cyclization ( Chen et al, 2011 ); and the DDXXD and NSE/DTE motifs in the C-terminal domain, which are responsible for metal-dependent ionization and substrate binding ( Chen et al, 2011 ). Homologous alignment analysis showed that CbTPS1 shared highest sequence identities with SBS (41.75%) from Salvia officinalis ( Wise et al, 1998 ; Figure 3 ), followed by AvBPPS (40.10%) from Amomum villosum ( Wang et al, 2018 ), LaBPPS (38.68%) from Lavandula angustifolia ( Despinasse et al, 2017 ), and LdBPPS (36.20%) from Lippia dulcis ( Hurd et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BPP is then dephosphorylated to form borneol ( Fig. 1B) (Wise et al, 1998;Despinasse et al, 2017;Hurd, Kwon & Ro, 2017;Wang et al, 2018). The BPPS gene has been functionally characterized in four species, Salvia officinalis, Lavandula angustifolia, Lippia dulcis and Amomum villosum.…”
Section: Introductionmentioning
confidence: 99%
“…BPP is then dephosphorylated to form borneol (Fig. 1b) (Croteau 1998;Despinasse et al 2017;Hurd et al 2017;Wang et al 2018). The BPPS gene has been functionally characterized in four species, Salvia officinalis, Lavandula angustifolia, Lippia dulcis and Amomum villosum.…”
Section: Introductionmentioning
confidence: 99%